PECULIARITIES OF PERFORMING THE DUTIES OF A LAWYER OF MILITARY AUTHORITIES IN THE AREA OF MILITARY OPERATIONS - Hanenko, Ihor; Shut, Vasyl; Knish, Mariia (European Journal of Interdisciplinary Issues, 2025)
The article is devoted to the study of the peculiarities of the activities of lawyers of military command and control bodies in the conditions of hostilities. The relevance of the study is stipulated by the need for legal support of military operations, compliance with international humanitarian law and protection of the rights of servicemen in the combat zone. The purpose of the article is to identify the key features of the activities of lawyers of military authorities and to develop the ways to improve the efficiency of their work in the combat zone. To achieve this goal, the study solved a number of tasks: the author characterizes the functional duties of lawyers of military command and control bodies; analyzes the regulatory and legal framework for their activities; identifies the peculiarities of performing the duties of lawyers of military command and control bodies in the combat zone; and offers recommendations for improving the efficiency of their activities. In the course of the study, the author used the methods of analysis, synthesis, induction, deduction and comparative legal method. Based on the results of the study, it is established that the effective activity of lawyers of military command and control bodies is critical for ensuring law and order, legality of military operations and protection of the rights of servicemen. At the same time, it has certain peculiarities that affect their work. Such features include: prompt response to changes in legislation, lack of access to adequate resources, increased responsibility in decision-making, confidentiality and preservation of military secrets, performance of duties in extreme conditions and speed of decision-making, adherence to military discipline and subordination to command. To improve the efficiency of lawyers' work, the author proposes a set of measures, including regular education and training, strengthening of cybersecurity measures, and improvement of interagency coordination. The practical significance of the study lies in the possibility of using its results to improve the legal support for the activities of the Armed Forces of Ukraine and to increase the efficiency of lawyers of military command and control bodies in combat conditions.